Effect of nintedanib on acute exacerbations of fibrosing interstitial lung diseases: a national database study in Japan - Hirokazu Urushiyama; Taisuke Jo; Wakae Hasegawa; Akira Yokoyama; Takahiro Ando; Yukiyo Sakamoto; Ryosuke Kumazawa; Kazuaki Uda; Nobuaki Michihata; Nobuyasu Awano; Matsui Hiroki; Kiyohide Fushimi; et al. (ERJ Open Research, 2022)
Background Acute exacerbation is a life-threatening event in patients with fibrosing interstitial lung diseases (ILDs). Although nintedanib reduces acute exacerbation incidence, its effectiveness during acute exacerbation is unclear. Methods Using data from the Diagnosis Procedure Combination database (September 2015–March 2020) in Japan, we identified patients with fibrosing ILDs who received intravenous injection of high-dose corticosteroid within 3 days post-admission and analysed their first hospitalisation. We performed overlap propensity score weighting to compare in-hospital outcomes between patients who received nintedanib within 14 days post-admission and those who did not. The primary and secondary outcomes were in-hospital mortality and length of hospitalisation in the patients discharged alive, respectively. Results Among the 6235 identified patients, 353 patients received nintedanib within 14 days post-admission. In-hospital mortality occurred in 13.7% and 6.0% patients in the control (n=5882) and nintedanib-treated (n=353) patients, respectively. The mean length of hospitalisation was 39.9 and 30.4 days in the control and nintedanib-treated patients, respectively. After overlap propensity score weighting, nintedanib treatment was significantly associated with lower in-hospital mortality in the adjusted cohort (OR 0.43, 95% CI 0.27–0.70; p=0.001). The mean length of hospitalisation in nintedanib-treated patients (30.7 days) was significantly shorter than that in the control group (37.5 days; p<0.001). Conclusions Nintedanib initiation during acute exacerbation was significantly associated with a lower risk of in-hospital death and shorter length of hospitalisation in patients with fibrosing ILDs. Our results elucidate the potential role of nintedanib in the treatment of acute exacerbation in patients with fibrosing ILDs. Further prospective studies are warranted.